PEMAHAMAN BUSHU MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG ANGKATAN 2019 UNIVERSITAS RIAU - Zilan Zailila; Arza Aibonotika; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: One of the difficulties when learning Japanese is when students are faced with kanji. Japanese learners struggle because of the large number of students, the variety of reading ways, etc. Kanji is basically a symbol of meaning. Bushu or radical is the basic character of kanji that shows meaning . Therefore , in this study, it will be seen how students understand bushu. This study uses a quantitative descriptive method. Using a test instrument that is used to determine the level of understanding of bushu in interpreting kanji in Japanese Language Eduaction students, the result show that the average bushu understanding of respondents is 77,79 which indicates that respondents have a good understanding of bushu.Key Word: Bushu, Kanji